HOW TO ENGAGE EMPLOYEE: THE INFLUENCE OF LEADERSHIP AND TEAM WORK - Alden Nelson (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
The term employee engagement relates to the level of an employee's commitment and it is has a connection to an organization. Employee engagement has emerged as a critical driver of business success in today's competitive marketplace. The purpose of this research to determine the correlation of employee engagement with leadership and team work in multinational company in Batam. The factors used in this study are leadership (X1), team work (X2), motivation (X3) and employee engagement (Y). The analysis technique used is multiple linear regression and the type of research includes explanatory research with hypothesis testing from primary data obtained from questionnaires. The data tested using Smart PLS 3.0 and found that the leadership no significant effet to employee engagement but team work and motivation have significant effect to employee engagement.